IKATAN SOSIAL PUNGUAN MAHASISWA SUKU BATAK TOBA DI PEKANBARU - Gaol, Yoan S Lumban; Jalil, Ashaluddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Nowadays, the phenomenon of people forming ethnic associations among students has become an important focus in social and cultural studies. Toba Batak students are trying to form an association to find friends from their clan overseas. This research aims to find out the basics of Batak students forming punguan in Pekanbaru as well as the meaning that punguan members get from their participation when joining the punguan. The subjects in this study were selected based on criteria previously determined by the author. This research uses descriptive qualitative research methods. The theory used is the social bond theory from Travis Hirschi. The research results that can be concluded in this study are that students formed clan collections in Pekanbaru in order to protect their ethnicity from being lost. The factors of the need for ethnic identity, social support from the surrounding area and awareness of cultural preservation are also reasons for the formation of student fees based on clans in Pekanbaru. Ethnic cohesiveness also maintains unity, closeness and bonds for each member of the punguan. Apart from that, clan levies also produce varied meanings for their members, starting from knowledge of their own clan's speech, getting support in various aspects of life and increasing their network of friends overseas. The conclusion of this research is that the basis for Toba Batak students forming local punguan is so that brotherly ties between clans remain strong and to avoid intermarriage within one clan. The meaning produced by students following the clan punguan is that the traditions of the Batak tribe are still preserved so that they are not eroded by modern times. The routine activities carried out in the punguan also make the bond between each member stronger.